Highly moisture-stable ferroelectric ammonium phosphate salt showing piezoelectric energy harvesting and rotation sensing applications - Kushwaha, Vikash; Prajesh, Neetu; Gopal, Animesh; Sahoo, Supriya; Deswal, Swati; Kirana, Antonysylvester; Shanmuganathan, Kadhiravan; Zareba, Jan K.; Boomishankar, Ramamoorthy (Journal of Materials Chemistry A, 2025)
Ferroelectric phosphate-based materials are known for their biocompatibility, dipole switching, and high thermal stability. In this context, we report a novel organic ferroelectric material, diisopropylammonium bis(4-nitrophenyl) phosphate (DIPABNPP), crystallizing in the monoclinic C2 space group. DIPABNPP exhibits a high second harmonic generation (SHG) efficiency 2.5 times higher than that of potassium dihydrogen phosphate (KDP). The ferroelectric nature of DIPABNPP was confirmed by the observation of a rectangular P-E hysteresis loop, which gave a saturated polarization value of 6.82 mu C cm-2. The ferroelectric polar domains of DIPABNPP, along with the bias-dependent amplitude butterfly and phase hysteresis loops, were visualized by piezoresponse force microscopy (PFM). Furthermore, the polydimethyl siloxane (PDMS) composites of DIPABNPP enabled the fabrication of humidity-resistant piezoelectric nanogenerators (PENGs) with energy harvesting and mechanical-electrical sensing capabilities. The top-performing 10 wt% DIPABNPP-PDMS device achieved a peak output voltage of 9.5 V and a charge storage efficiency of 81.8%, successfully powering 53 LEDs. Additionally, its rapid response time of 18.5 ms enables precise rotation sensing capabilities, suggesting potential applications in motion monitoring, such as revolution per minute (RPM) counting. We also present a unique and refined method for obtaining the output work efficiency (OWE) parameter, which quantifies the ratio of harvested electrical energy to the maximum elastic energy stored in the composite device, taking into consideration several key parameters during the PENG measurements. For the 10 wt% DIPABNPP-PDMS composite, an OWE of 13.1% was achieved, highlighting both its current performance and potential for optimization. This metric provides a standardized approach for evaluating PENGs, addressing a critical gap in assessing mechanical-to-electrical energy conversion efficiency.